2016
DOI: 10.1111/exd.13065
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of BRAF mutation status in circulating tumor DNA of metastatic melanoma patients at baseline

Abstract: Circulating tumor DNA is a promising non-invasive tool for cancer monitoring. The main objective of our work was to investigate the relationship between mutant BRAF DNA in plasma and clinical response. Thirty-eight stage IV patients with a V600 mutated BRAF melanoma were included prior to any treatment. DNA was extracted from plasma and mutant DNA was detected using the amplification-refractory mutation system method. Before the beginning of any treatment, the corresponding BRAF mutation was detected in 29 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
(43 reference statements)
2
34
0
1
Order By: Relevance
“…Some previous reports have shown that low baseline ctDNA is a good predictor of response to treatment, longer PFS, and even OS in targeted therapy (12,13,20). Although there was no statistical significance between BRAF V600E in ctDNA and clinical benefit, patients with wild-type BRAF ctDNA have longer PFS and OS than mutant type which supports the findings of previous reports.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Some previous reports have shown that low baseline ctDNA is a good predictor of response to treatment, longer PFS, and even OS in targeted therapy (12,13,20). Although there was no statistical significance between BRAF V600E in ctDNA and clinical benefit, patients with wild-type BRAF ctDNA have longer PFS and OS than mutant type which supports the findings of previous reports.…”
Section: Discussionsupporting
confidence: 81%
“…LDH is the only blood-based biomarker incorporated into the staging system, as elevated levels of LDH are associated with significantly decreased survival (19). Both BRAF V600E in ctDNA and LDH in the blood are good prognostic markers and are thought to be useful in the follow-up of patients with melanoma (20). LDH is neither sensitive nor specific, and other studies have shown that ctDNA is more consistent and informative than LDH (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In a 48-patient cohort treated by MAPK inhibitors or immunotherapies, low baseline ctDNA was a good predictor of response to treatment and longer PFS [30]. More recently, the presence of detectable levels of ctDNA at baseline strongly correlated with longer OS [20]. All these studies suggest that rising or elevated ctDNA levels may predict poorer clinical outcome.…”
Section: Clinical Applications For Ctdna In Melanomamentioning
confidence: 99%
“…The superiority of measuring ctDNA over that of LDH levels was demonstrated in three other patients for whom ctDNA levels more accurately reflected the evolution of disease than those of LDH, as the latter tends to increase following immunotherapy [35]. In contrast, two other studies reported a positive correlation between ctDNA and LDH levels [20, 30]. …”
Section: Clinical Applications For Ctdna In Melanomamentioning
confidence: 99%
“…1 2 Similarly, overall survival (OS) was significantly associated with BRAF V600mut status in ctDNA prior to any targeted therapy. 3 Furthermore, a significantly higher PFS was found for patients in whom ctBRAF V600mut became undetectable at some time point after initiation of targeted therapy. 4 From 2012 to 2014, 85 patients from the onco-dermatology department of the Saint-Louis Hospital (Paris, France) presenting unresectable stage III (n=12) or stage IV (n=73) melanoma with BRAF V600E mutated lesions at targeted therapy initiation (BRAF inhibitors, vemurafenib or dabrafenib) were included in this retrospective study after signed informed consent.…”
mentioning
confidence: 99%